MASA KODIFIKASI HADIS Meneropong Perkembangan Ilmu Hadis Pada Masa Pra-Kodifikasi hingga Pasca Kodifikasi - Riska Yunitasari (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2020)
In the course of the development of traditions from the time of the Prophet, Companions, Tabi'in to contemporary experiences a very significant journey, starting from the traditions that were conveyed through oral orally to develop into writing, because it is a concern about the disappearance of the Prophet's traditions, of course the writing requires more time than when compiling the Qur'an. (1) When did the Hadith start to be officially codified ?, At which time the development of the hadith reaches its peak, so that efforts are needed to counter the spread of false traditions. (2) how is the development of hadith after the hadith is codified? has been packaged in such a way as an application so that in reviewing the hadith becomes easier.